Once More with Feeling: Re-investigating the Smuttynose Island Murders - Chare, Nicholas (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2016)
During the night of March 5, 1873, two Norwegian women were murdered on Smuttynose Island in the Isles of Shoals off the New Hampshire coast. The crime has attracted significant and enduring attention. This article examines two depictions of the murders—Celia Thaxter’s 1875 essay “A Memorable Murder” and Kathryn Bigelow’s film from 2000 The Weight of Water, an adaptation of Anita Shreve’s novel of the same name. Employing psychoanalytic thinking inspired by the theories of Melanie Klein and Ruth Riesenberg-Malcolm, I examine how these literary and filmic re-enactments facilitate the reviving of the past in the present and how they foster an experience akin to transference as it is conceived in the analytic situation.